Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae) - Freyhof, Jörg; Kaya, Cüneyt; Turan, Davut (Zootaxa, 2017)
Oxynoemacheilus kentritensis, new species, is described from the Botan drainage, a tributary to the upper Tigris. It is distinguished from other Oxynoemacheilus species in the Tigris drainage by having a complete lateral line, long barbels, flank and back completely covered by scales and flank behind dorsal-fin base with large, dark-brown, vertically elongated blotches or bars.